Circular Section Metal Wall cut-off Waveguide Accurate Calculation when used as a Standard Attenuator (Global Journal of Science Frontier Research, 2024)
In this paper, the mathematical analysis is carried out from many angles, so that the theoretical calculation problem of the circular metal wall cut-off waveguide used as a premary attenuation standard is completely solved, and the Chinese national standard of the attenuation quantity is established. The benchmark was completed by the Chinese National Institute of Metrology (NIM) with an accuracy of 5×10 -5 ; Reach the international advanced level. The calculation accuracy provided in this paper is 10 -6 ~10 -7 . This is a good example of a project combining theory and practice.
Keywords: cut-off waveguide attenuator; national standard for attenuation; the accuracy of the attenuation constant